Effect of personality traits and demographics on the employment status of Latin American students - Barrera Verdugo, Gustavo Alfonso.; Cadena Echeverría, Jaime.; Villarroel Villarroel, Antonio José.; Contreras Fuenzalida, Michelle. (Richtmann Publishing, 2023)
Personality traits have been highlighted as factors that affect workers’ behaviour, such as their performance or labour engagement. However, little is currently known about the personality differences between Latin American university students who perform self-employment activities, those who are dependent workers and those who are nonworkers. This research fills this knowledge gap by assessing the influence of the personality traits of 758 university students from Latin America on their employment status. In addition, the effect of gender and age cohort on students’ employment status is assessed. A logistic regression analysis is conducted using the personality traits of the Big Six model, gender and belonging to the millennial generation as independent variables has been conducted. The results support the significant effect of openness, conscientiousness and extraversion on students' employment status. Likewise, effects of gender and age are found. The results contribute to a better understanding of how individual conditions may affect the work activity of university students with regard to dependent employment, self-employment and work inactivity. In addition, the results can guide efforts to support entrepreneurship through the design of effective training programmes according to the students' personality traits and demographic characteristics.
Keywords: Age generation; Employment status; University students; Genero; Personalidad